Postoperative nutritional support of the patient with gut gangrene-a case report - Samra Imran; Afifa Tanweer (BMC, 2019)
Abstract Background Bowel necrosis is a commonly observed condition in elderly patients with longstanding diabetes. In such condition, intestinal resection is usually performed for the removal of the gangrenous part. Post-surgical dietary management after bowel resection poses several challenges for the health care team. Case presentation The case presented in this study is that of an elderly diabetic male who developed acute renal failure as a result of neglect in post-surgical feeding after intestinal resection. After the intervention by a trained dietitian, a transitional diet was planned and successfully executed, resulting in reversal of acute renal failure, dehydration, and post-surgical stress. Several complications including hepatic dysfunction and mouth ulcers were resolved through well-planned transitional diet. The patient was finally discharged in a stable health condition and was regularly followed up for any nutritional or medical issues. Conclusion Neglects in nutritional care of patients can have severe implications including development of medical complications, resulting in increased length of hospital stay, augmenting the disease stress of the patient and family, and finally the preventable drainage of several human and monetary resources. Therefore, recognition of nutritional intervention as an important part of in-hospital health care may have social as well as economic impacts.